An Analysis of the Vocabulary Practice Program at Modern Islamic Boarding School - Zainudin Zainudin (Syntax Idea)
This study aims to describe and analyze about vocabulary practice program. The results of this study are expected to be used to improve the existence of vocabulary practice program. This study takes the background at MA Nurussalam Modern Islamic Boarding School Sidogede Belitang OKU Timur. The research was designed in qualitative interpretive research design and used descriptive survey in the type of cross-sectional survey. The data collection was conducted by observation, interview and distributing questionnaires. The data has been collected from the result of this study was analyzed by describe using tabulated the data graphically in the tables and discussed the explanation of each respondent’s answer through questionnaires and from that can be drawn the conclusion. The result of this study is shown: (1) this program played a role to improve the quality of speaking proved by increasing student’s competence of vocabulary and comprehension which hold in a week five times in 30 minutes after Shubuh prayer and school time and seemly made teaching and learning more attractive and be better (2) 84.9% of respondent agreed that student could improve their English ability by participation support agendas.